Effectiveness of Problem Based Learning Integrated STEAM on Students’ Mathematical Problem Solving Ability - Rahmatjati, Abdul Mu'iz; Ardiansyah, Adi Satrio; Rochmad, Rochmad (Unnes Journal of Mathematics Education, 2023)
This study aims to determine the effectiveness of the Problem Based Learning (PBL) integrated STEAM on students' mathematical problem solving abilities. The population in this study were students of class VIII in Junior High School 1 Pringapus. The sample in this study were students of class VIII B as the experimental group and class VIII A as the control group. The sampling technique in the quantitative method in this study used a simple random sampling technique. The data collection technique used in this study was a test technique to obtain data on students' mathematical problem solving abilities. Based on the results of the study, it can be concluded that: (1) the average test results for students' mathematical problem solving abilities using the PBL integrated STEAM achieve individual completeness of 75; (2) the proportion of students' mathematical problem solving ability test results using the PBL integrated STEAM achieves 85% classical completeness; (3) the average test results for students' mathematical problem solving abilities with the PBL integrated STEAM are more than the average test results for students' mathematical problem solving abilities with the PBL; (4) the completeness proportion of students' mathematical problem solving ability test results using the PBL integrated STEAM is more than the completeness proportion of students' mathematical problem solving ability test results using the PBL. So, it can be concluded that the PBL integrated STEAM is more effective than the PBL.